Romani or Pseudo-Romani? On the Lord's Prayer in 'Nubian' by Jean-Baptiste Gramaye (1622). Issue 2 (November 2016) - Adiego, Ignasi-Xavier
Abstract : The alleged Romani version of the Lord's Prayer edited by Jean-Baptiste Gramaye in his book Oratio Dominica centum et amplius diuersis expressa linguis seu dialectis ex uariis auctoribus laudatis in libro de litteris et linguis uniuersi orbis, Bruxelles, 1622, is in all probability a fraud. The same verdict can be delivered on the version of the same text in Rotwelsch (German cant) collected in the same publication.